The origins of Scottish nationhood - Davidson, Neil, 1957-2020 (Pluto Press, 2000)
'The great merit of The Origins of Scottish Nationhood' is that it seeks to encourage clear thinking about the national condition.' Allan Massie in The Times Literary Supplement,